Quality of life of prematurely born schoolchildren; the caregiver's report and the child's self-report - Martini, Juliana Aparecida [UNESP]; Perosa, Gimol Benzaquen [UNESP]; Pereira Padovani, Flavia Helena [UNESP] (Abrasco-assoc Brasileira Pos-graduacao & Saude Coletiva, 2019)
This study compared assessments concerning the quality of life of prematurely born schoolchildren based on two instruments and compared the assessments of children with those of their caregivers. A total of 57 prematurely born children of both sexes aged between five and eight years of age participated in the study. The caregivers completed an instrument based on funcionality (HUI3) while an autoquestionnaire based on the theory of wellbeing (AUQEI) was applied to both children and caregivers. The correlation between the caregivers' assessments measured by two instruments, and the assessments between the different respondents was calculated. The results show that 51.9% of the children considered their quality of life to be impaired; a high level of agreement was found with the caregivers' assessments. According to the HUI3, caregivers considered that the quality of life of children was mildly impaired. No statistically significant association was found between the answers provided by the caregivers' to both scales. The perception that the quality of life of prematurely born children is discussed as well as the level of agreement found between children and caregivers when the same instrument was used and lack of consensus between the instruments based on different theoretical frameworks.
Keywords: Quality of life; Child health; Premature birth; Evaluation